The Role of Social Health Insurance in Achieving Universal Health Coverage in Asia: A Systematic Review - Jauhar, Afaf; Nadjib, Mardiati (UI Scholars Hub, 2024)
Universal Health Coverage (UHC) aims to ensure that all individuals have access to essential health services without financial hardship. Social Health Insurance (SHI) is critical in achieving this goal, especially in low- and middle-income countries. This systematic review explores the role of SHI systems in advancing UHC across 14 Asian countries, focusing on healthcare access, financial protection, and equity. A comprehensive search across PubMed, Scopus, and ScienceDirect identified 768 articles, and 37 studies were selected after screening, following the PRISMA guidelines. The chosen studies cover countries with varying SHI models across Asia. The findings reveal that high-income countries such as Japan, South Korea, and Singapore have made notable progress toward UHC. However, they face challenges related to aging populations and financial sustainability. In Thailand, the Universal Coverage Scheme (UCS) has achieved near-universal coverage, while Malaysia and Indonesia struggle with rural healthcare access and specialized care. In lower-middle-income countries like India, Vietnam, and Bangladesh, progress in financial protection is evident, but gaps persist in outpatient care and equitable access. Nepal and Cambodia face significant barriers due to economic and geographical constraints. This review underscores the critical role of SHI in advancing UHC. It highlights the need for policy reforms, innovative financing, and targeted interventions to strengthen SHI systems and improve equitable healthcare access across all Asian populations.